Hyadaphis foeniculi on anise crop in Pernambuco State - Ferreira, Rachel Gonçalves; Sousa-Silva, Carlos Roberto (Pesquisa Agropecuaria Brasileira, 2004)
Hyadaphis foeniculi (Passerini, 1860) (Hemiptera: Aphididae) was observed causing damage on anise crop, Pimpinella anisum L., in the Meridional “Agreste” region of Pernambuco State, Brazil. This is the first report of this species in the region.